Manajemen Pemasaran dalam Meningkatkan Animo Pendaftar di SMP Kristen 1 Amanuban Timur, Kecamatan Amanuban Timur, Kabupaten Timor Tengah Selatan - Oma Baceba Banfatin; Imelda Marina Djira; Nimrot Doke Para (MAMEN: Jurnal Manajemen, 2026)
This research is motivated by the decline in the number of applicants at Christian Junior High School (CJHS) 1 Amanuban Timur in the last three years, namely from 110 students (2022) to 94 students (2023), and 71 students (2024). This condition encourages the need for appropriate marketing management strategies to increase public interest. The purpose of this study is to describe how school marketing management is implemented through planning, organizing, implementing, and controlling. The research method uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The research informants consisted of three subjects: the principal, vice principal, and public relations officer. Data were analyzed through systematic reduction, presentation, and drawing conclusions. The results of the study indicate that marketing management at CJHS 1 Amanuban Timur includes four functions, namely planning: marketing management has been carried out through meetings with the school and committee, preparation of work programs, and promotional strategies such as creating brochures, banners, social media, and socialization to elementary schools. The organization of Admision of New Students is carried out by forming a committee based on the Principal's Decree and is equipped with a description of the duties of each section. Promotional activities were implemented in a varied manner. Control was provided through direct supervision by the principal and vice principal. The conclusion was that marketing management was functioning effectively, but strategic innovation, the development of internal technical guidelines, and evaluation instruments were still needed to increase enrollment interest more effectively.